Iterative Learning Control for Switched Systems in the Presence of Input Saturation. Issue 2 (2020) - Pakshin, Pavel; Emelianova, Julia; Rogers, Eric; Galkowski, Krzysztof
Abstract: The paper considers iterative learning control for differential and discrete switched linear systems with control input saturation. A new design is developed based on the use of common vector Lyapunov functions. An example demonstrating the features and advantages of the new design is given.